SKALA RESILIENSI PADA MASYARAKAT KOTA SURABAYA - Amiroh Untsal Asad; Hafnidar Hafnidar (CV. Syntax Corporation Indonesia, 2023)
Resilience is defined as an individual's ability to overcome adversity and deal with any psychological stressors. Resilience reflects the ability to bounce back and take advantage of opportunities. In the context of the people of Surabaya, they have to face various serious problems, such as dense population density, lots of pollution, and a high level of competition for work. This pressures leads to a tendency to experience various mental disorders and psychological vulnerabilities. Under these conditions, researcher created a psychological scale to measure the level of resilience in the people of Surabaya City. This psychological scale refers to the theory of Reivich and Shatté (2006) about the construct of resilience which consists of seven dimensions, namely emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. A total of 38 women and 16 men (N = 54) with an age range of 17-50 years participated in this study. The research method used is a Likert scale model. The results of the study found that 32 of the 44 items tested were valid with a item-total correlation coefficient of more than 0.300. The Cronbach's Alpha value is calculated at 0.909. Thus, this Resilience Scale can be used in the context of the people of Surabaya City